Lecture Presentations Combined with Comic Story-Telling to Increase the Knowledge and Understanding of Elementary and Junior High School Students about Drugs Concerning Self-Medication Behavior - Miatmoko, Andang; Mufariha, Mufariha; Retnowati, Dini; Paramanandana, Abhimata; Sugiyartono, Sugiyartono; Sari, Retno; Purwanti, Tutiek; Isadiartuti, Dewi; Hendradi, Esti (Journal of Community Research and Service, 2022)
Self-medication practice can result in medication errors due to limited public knowledge of pharmaceutical medicine, especially among school-aged adolescents, who are prohibited from doing self-medication. This study aimed to evaluate the students' knowledge and understanding of pharmaceutical medicine, pharmacists, and self-medication, and also the awareness to be wise and smart in responding to the use of pharmaceutical products for maintaining public health. The study was carried out by conducting the lecture on drugs and self-medication through a classical presentation and comic story to students of SDN Keputih 245 Elementary School and SMPN 19 Junior High School, Surabaya. Moreover, DAGUSIBU dance was also practiced. The students actively engaged in the class during the presentation. The results of the pre-and post-test evaluations showed that this lecture method had succeeded in increasing junior high school students' knowledge about medicine and DAGUSIBU. On the other hand, the pre-test scores of Elementary School students were better than the post-test, except for new knowledge related to the drug logo and classification. It suggests that the delivery methods were inappropriate for elementary school students. It can be concluded that school-age adolescents, especially in elementary and junior high schools, need assistance during self-medication. This community service activity by a presentation and comic telling methods successfully improved the knowledge of SMPN 19 Junior High School about drugs and DAGUSIBU; however, it needs a more straightforward explanation with attractive learning methods for delivering a lecture to Elementary School students.